Vantagens de aglomerações no Brasil, as mudanças nos fluxos migratórios e no perfil dos migrantes entre 1980 e 2010 - Campelo, Thiago Carneiro (2018)
This article is an effort in better understand specific migration through brazilian urban areas, occurred more intensely since 1980, investigating wage and skill dynamics, besides another migrants aspects and qualities, and the influence of more populated cities, where higher wages are perceipt. The analysis uses data of four IBGE Censos, namely, 1980, 1991, 2000 and 2010 and bases in works by authors dealing with the effects known as agglomeration economies, perceived as the cities go bigger in population. Whereas new metropolis were arising at national scenarium, studies show that the tipic migration flows have changed (mainly from rural-urban to urban-urban), but have the migrants profile changed too? A detailed investigation points that contemporary migration flows are more associated to young and more nomads generations, looking for acquire and share experience, to find specific jobs and wages that recognizes their individuals skills. In big cicies, migrants average wage are bigger. Mainly in the 2000 and 2010, although education levels of migrants are lower that of people who has born in those places, showing that not only education levels, but also the migration profile influences in wage, as the bibliographic references shows (agglomeration economies).